MENINGKATKAN KEMAMPUAN BERBAHASA ANAK TUNAGRAHITA RINGAN MELALUI BERCERITA ULANG - , MADECHAN (Pendidikan Dasar, 2008)
Abstract; This research aimed to answer question ”Do retell story using story book can improve speech ability of conducted grade 4 in special need school Bangun Bangsa Surabaya”. This research was in special need school Bangun Bangsa Surabaya with subject research were grade 4 students around 4 children. This research consisted of independent variable that was retell story and dependent variable was speech ability.Design that was used in this research was one group pre test post test design. From data analysis above researcher indicated there any improvement speech ability in mentally retarded student through retell story by using descriptive analysis method 0,56 percentage after performed treatment. Retell story could be used as a method to improve speech ability for mentally retarded student grade 4 in SBK Bangun Bangsa Surabaya.